I Wish We Could Fast Forward It: Negotiating the Practice of Preaching (Homiletic, 2019)
Though recent decades in empirical homiletics have significantly contributed to the understanding of what happens in preaching from the listener’s point of view, empirical homiletics needs to do another turn and ask: What do listeners do with preaching? This article introduces children into empirical homiletics as a new group of listeners, and by a thick description of preaching as a practice. Children seldom become full participants in the practice of preaching, mainly because they do not understand what preaching is, they struggle to follow the rules, and they have different ends for the practice than the preachers. One implication for homiletics is that if preaching is considered a practice, it can also be taught. This might help children more easily become participants in the practice of preaching.